An Alternative of Rural Development: The Rout of Pisco as Tourist Resource (Elqui Valley, Chile) [Alternativas No Tradicionales de Desarrollo Rural: La Ruta del Pisco Como Recurso Turístico (Valle de Elqui, Chile)] - Lacoste, P (Universidad de Tarapaca, 2014)
The Route of Pisco Elqui Valley emerges as a complementary proposal of tourism of sun and beach and astrotourism already bound in the IV Region of Coquimbo, Chile. While not formally exist yet as this route has actually begun to operate due to its considerable resources: scenic beauty, infrastructure, facilities, equipment and certain tourist superstructure. This route also includes the initial section of the old route from La Serena brandy extended to Potosi and Buenos Aires, with an area of over 6,000 km, the oldest terrestrial long-distance trade route of the Southern Cone of America. With its strengths and weaknesses, the organization of these elements to create Pisco Route can generate a considerable contribution to the development of wine tourism and rural tourism, to provide a boost to regional economic development. Pisqueras cases are analyzed in the area such as Los Nichos, Mistral, Capel y Tres Cruces. © 2014, Universidad de Tarapaca. All rights reserved.